2001
DOI: 10.1084/jem.193.3.375
|View full text |Cite
|
Sign up to set email alerts
|

Clustered Mutations in HIV-1 Gag Are Consistently Required for Escape from Hla-B27–Restricted Cytotoxic T Lymphocyte Responses

Abstract: The immune response to HIV-1 in patients who carry human histocompatibility leukocyte antigen (HLA)-B27 is characterized by an immunodominant response to an epitope in p24 gag (amino acids 263–272, KRWIILGLNK). Substitution of lysine (K) or glycine (G) for arginine (R) at HIV-1 gag residue 264 (R264K and R264G) results in epitopes that bind to HLA-B27 poorly. We have detected a R264K mutation in four patients carrying HLA-B27. In three of these patients the mutation occurred late, coinciding with disease progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
416
2
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 416 publications
(434 citation statements)
references
References 52 publications
14
416
2
2
Order By: Relevance
“…Indeed HIV has been shown to escape from CTL immune surveillance by mutation at P2 [3,30], and this escape is mediated by immune selection pressure [31,32]. The viral capsid interactions between two neighboring p24 molecules are mediated by residues within the HIV epitope, and it appears that modification of the P6 leucine to methionine permits mutation of the P2 arginine without significant loss of viral fitness [31]. A P6 L-to-M mutation occurs prior to, [26] were based on the structure of the KIR2DL1-HLA-Cw4 complex [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed HIV has been shown to escape from CTL immune surveillance by mutation at P2 [3,30], and this escape is mediated by immune selection pressure [31,32]. The viral capsid interactions between two neighboring p24 molecules are mediated by residues within the HIV epitope, and it appears that modification of the P6 leucine to methionine permits mutation of the P2 arginine without significant loss of viral fitness [31]. A P6 L-to-M mutation occurs prior to, [26] were based on the structure of the KIR2DL1-HLA-Cw4 complex [27].…”
Section: Discussionmentioning
confidence: 99%
“…or coincidentally with, mutation of the P2 arginine to threonine, lysine or aspartate [31,32]. Studies have shown that the M6 mutant retains full binding potential to the HLA-B*2705 groove [30,31], and the HLA-B*2705-HIV structure indicates that the P6 leucine side chain, being solvent-exposed, plays little role in stabilizing the HIV epitope's binding to HLA-B*2705.…”
Section: Eur J Immunol 2005 35: 341-351mentioning
confidence: 99%
See 1 more Smart Citation
“…If escape occurs in variable viruses, it is highly epitope dependent, as is clear from detailed studies of HLA-B27-restricted epitopes in HIV [71][72][73]. Some of these epitopes may fall in regions that are 'constrained' or stable within the virus, due to conserved structure or function and multiple 'compensatory' mutations may need to accumulate, which does not occur readily.…”
Section: Success Versus Failure Of T Cell Responses: the Potential Romentioning
confidence: 99%
“…Although the role of antigenic variation in HLA class I-restricted epitopes has been widely studied [18][19][20][21], work on the influence of HIV-1 antigenic variation on HLA class II-restricted CD4 T-cell responses has been limited, probably due to the difficulty of detecting these responses in HIV-1 infected individuals at any stage of infection. The objective of this study was to determine whether differences in the amino acid sequences of envelope glycoproteins from HIV-1 isolates of infected children would influence the ability to detect Env-specific Thelper cell responses.…”
Section: Introductionmentioning
confidence: 99%